STUDI KEMITRAAN DESA ADAT DENGAN PELAKU USAHA WISATA UNTUK PENGEMBANGAN EKOWISATA BIOROCK DI DESA PEMUTERAN - Made Arie Wahyuni (Universitas Pendidikan Ganesha, 2016)
This research was conducted in the village of Pemuteran with goal 1) identify potential tourism partnership for the development of ecotourism Biorock in Pemuteran, 2) describe the form of partnerships undertaken indigenous villages in the development of ecotourism Biorock in Pemuteran Beach, and 3) to analyze the contribution of partnership in development Biorock ecotourism in Pemuteran Bay. The method used is a survey method to gather information that is qualitative, and is supported by direct observation in the field, and in-depth interviews (indepht interview). The sample is determined by using purposive. The data analysis was done by using qualitative descriptive analysis of the tourism potential partnership, forms partnerships with entrepreneurs indigenous villages travel. As for the contribution of a partnership for the development of ecotourism in Attractions Biorock in the village of Pemuteran using quantitative descriptive analysis. The results showed: (1) The potential of tourism covers four aspects that must be managed. The management will be easier if partnership with other parties. The partnership aspect that attractions such as coral reef cultivation, travel accommodations, such as hotels and restaurants, such as access roads and signs rambunya and institutional form of the governing body; (2) There are two Forms Partnership Contract Governance is a form of partnership where private sector partners were given the responsibility for managing the infrastructure / facilities owned by the government or the indigenous villages. Aspects of the contracted is an office within an organization / management course, and Contract Concessions occur because businesses Travellers own the land, it can open a business in accordance with their ability; (3) Form partnerships contribute positively to the development of ecotourism Biorock. Both forms of partnerships that contribute to the development of ecotourism is a form of partnership governance, and concessions. Keywords: Partnership, Village People, Business Executors Tourism, Ecotourism